Single Event Upset Study of 22 nm Fully Depleted Silicon-on-Insulator Static Random Access Memory with Charge Sharing Effect - Chenyu Yin; Tianzhi Gao; Hao Wei; Yaolin Chen; Hongxia Liu (Micromachines, 2023)
In this paper, the single event effect of 6T-SRAM is simulated at circuit level and device level based on a 22 nm fully depleted silicon-on-insulator (FDSOI) process, and the effects of charge sharing and bipolar amplification are considered in device-level simulation. The results demonstrate that, under the combined influence of these two effects, the circuit’s upset threshold and critical charge decreased by 15.4% and 23.5%, respectively. This indicates that the charge sharing effect exacerbates the single event effects. By analyzing the incident conditions of two different incident radius particles, it is concluded that the particles with a smaller incident radius have a worse impact on the SRAM circuit, and are more likely to cause the single event upset in the circuit, indicating that the ionization distribution generated by the incident particle affects the charge collection.